Experiências de escolarização de alunos com deficiência da Universidade Federal do Pará no Campus de Altamira - CONCEIÇÃO, Samantha Costa (2023)
This work has as its object of study the schooling experiences of students with disabilities in a Higher Education Institution. And it aims to identify and analyze the schooling trajectories of students with disabilities who entered undergraduate courses, in which the central question of the problem is: How does the experience of disability mark the trajectory of schooling in higher education? As a result, this is a field research with a qualitative approach. And to give centrality to the students' experiences, it was decided to use a questionnaire. Thus, the research reveals that the academic trajectory is unique for each subject. And in general, the Federal University of Pará on the Altamira campus has sought to contribute to the performance of inclusion, but it needs to improve a lot and overcome the barriers that still exist, aware that in order to build a culture of accessibility it is essential to think about access , accessibility, learning and permanence.